Budaya Pendidikan dan Budaya Organisasi Serta Jaringan Komunikasi Dalam Pendidikan - Rifai, Muhammad; Syahputra, Muhammad Rizki; Thaiyibah, Afifah; Mardiana, Mardiana; Pohan, Hadi Lapian (MODELING: Jurnal Program Studi PGMI, 2024)
This study examines the interaction between educational culture, organizational culture, and communication networks in the context of Al-Hadi School. Using a qualitative case study approach, this research digs deeper into the fundamental values, norms and practices that shape the school learning environment. The findings reveal that Al-Hadi culture emphasizes discipline, adherence to religious values, and innovative teaching methods. While these elements have fostered a strong sense of community, they have also influenced the development of formal and hierarchical communication networks.